2017
DOI: 10.4103/2249-4863.214954
|View full text |Cite
|
Sign up to set email alerts
|

Profile of drug-resistant tuberculosis in Western Maharashtra

Abstract: Context:Drug-resistant tuberculosis (TB) strains have evolved mainly due to incomplete or improper treatment of TB patients and are one of the hurdles in controlling TB problem. It is better to understand the magnitude and comorbidities associated with drug-resistant TB.Aim and Objectives:(1) To study some of the sociodemographic profile and history of TB treatment of drug-resistant TB cases. (2) To study their drug-resistance pattern and their comorbidity profile.Settings and Design:It was a record-based stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…describing the profile of drug-resistant tuberculosis (DR-TB) patients referred to the State TB Training and Demonstration Center, Maharashtra (STDC). [ 1 ] The study reported that most DR-TB were male and below 35 years of age which highlights the enormous threat posed by the increasing burden of DR-TB on India's vast demographic dividend. I have the following queries and request for clarifications on a few key observations from the study.…”
mentioning
confidence: 99%
“…describing the profile of drug-resistant tuberculosis (DR-TB) patients referred to the State TB Training and Demonstration Center, Maharashtra (STDC). [ 1 ] The study reported that most DR-TB were male and below 35 years of age which highlights the enormous threat posed by the increasing burden of DR-TB on India's vast demographic dividend. I have the following queries and request for clarifications on a few key observations from the study.…”
mentioning
confidence: 99%